EXPLORING THE ENGAGEMENT OF STUDENTS WITH LIBRARY RESOURCES AND SERVICES: A CASE STUDY OF BANGALORE CITY UNIVERSITY - Kishora H V (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The study aimed to explore the utilization of library resources and services by post-graduate students. The main objectives of this study are to identify the purpose of the visit to the library, the frequency of use of library resources and services, and assess the level of knowledge about the use of library resources/computers/Internet. The scope of this study is for post-graduate students at Bangalore City University in Bangalore, Karnataka. A survey was conducted using 135 structured questionnaires to collect data from post-graduate students in selected universities. The study found that 77 (57.03%) were male, 58 (42.96%) females participated in this research. 73 (54.07%) were from the science discipline, and 62 (45.92%) were from the social science discipline. The majority of respondents fall into the age group of 21-23, comprising nearly 63% of the total respondents. Furthermore, the majority of respondents, comprising nearly 59%, utilize the library daily. 69.62% of respondents indicated it as their primary purpose to get books issued/returned/to read books. The majority of respondents use e-books to some extent, with 26.66% using them to a very large extent and 23.70% to a large extent. Based on the study’s results, possible recommendations were made to overcome the challenges.